Tonsillectomy indication in adult with chronic tonsillitis: a case report - Komang Soniananda Pradnyana Putri (Intisari Sains Medis, 2021)
Introduction: Tonsils are the body's defense against viruses or bacterial antigens that enter the tonsils. These pathogens can cause inflammation and formed focal infection. Either persistent or recurrent infection of the palatine tonsils occurs in chronic tonsillitis. Tonsillectomy is surgical procedure that removed the entire palatine tonsils. It is performed if conservative and medical management failed to relieve symptoms and if indicated by the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) consensus published 1995.Case description: A 30 years old male, complained a lump in his throat for about a year and had worsened for the previous 1.5 months. The patient also had difficulty in breathing, especially during sleep and snored. The patient had received treatment and got better. However, some complaints such as fever, cough, runny nose, difficulty and painful swallowing appear more than three times a year. The patient was alert, vital signs and general examination are within normal limits. Throat examination revealed T2 - T3 tonsils, hyperemic + / +, dilated crypts + / +, detritus - / -, midline uvula with hyperemic mucosa. The patient was diagnosed with chronic tonsillitis and undergone Tonsillectomy.Conclusion: Tonsillectomy is indicated in patients with enlarged tonsils that cause upper airway obstruction and recurrent episode of tonsil infections more than three times per year despite adequate medical therapy.